From Monsoons to Microbes: Understanding the Ocean's Role in Human Health - National Research Council (The National Academies Press, 1999)
What can sharks teach us about our immune system? What can horseshoe crabs show us about eyesight? The more we learn about the ocean, the more we realize how critical these vast bodies of water are to our health and well-being. Sometimes the ocean helps us, as when a marine organism yields a new medical treatment. At other times, the ocean poses the threat of coastal storm surges or toxic algal blooms. From Monsoons to Microbes offers a deeper look into the oceans that surround us, often nurturing yet sometimes harming humankind. This book explores the links among physical oceanography, public health, epidemiology, marine biology, and medicine in understanding what the ocean has to offer. It will help readers grasp such important points as:
Keywords: Earth Sciences

Starting Out Right: A Guide to Promoting Children's Reading Success - National Research Council (The National Academies Press, 1999)
A devastatingly large number of people in America cannot read as well as they need for success in life. With literacy problems plaguing as many as four in ten children in America, this book discusses how best to help children succeed in reading. This book identifies the most important questions and explores the authoritative answers on the topic of how children can grow into readers, including:
Keywords: Education

Reducing Disaster Losses Through Better Information - National Research Council (The National Academies Press, 1999)
Losses of life and property from natural disasters in the United States-and throughout the world-have been enormous and the potential for substantially greater future losses looms. It is clearly in the public interest to reduce these impacts and to encourage the development of communities that are resilient to disasters. This goal can be achieved through wise and sustained efforts involving mitigation, preparedness, response, and recovery. Implementing such efforts, particularly in the face of limited resources and competing priorities, requires accurate information that is presented in a timely and appropriate manner to facilitate informed decisions. Substantial information already exists that could be used to this end, but there are numerous obstacles to accessing this information, and methods for integrating information from a variety of sources for decision-making are presently inadequate. Implementation of an improved national or international network for making better information available in a more timely manner could substantially improve the situation. As noted in the Preface, a federal transition team is considering the issues and needs associated with implementing a global or national disaster information network as described in the report by the Disaster Information Task Force (1997). This National Research Council report was commissioned by the transition team to provide advice on how a disaster information network could best make information available to improve decision making, with the ultimate goal of reducing losses from natural disasters. The report is intended to provide the basis for a better appreciation of which types of data and information should be generated in an information program and how this information could best be disseminated to decision makers.
Keywords: Earth Sciences; Conflict and Security Issues

Making Climate Forecasts Matter - National Research Council (The National Academies Press, 1999)
El Nino has been with us for centuries, but now we can forcast it, and thus can prepare far in advance for the extreme climatic events it brings. The emerging ability to forecast climate may be of tremendous value to humanity if we learn how to use the information well. How does society cope with seasonal-to-interannual climatic variations? How have climate forecasts been used—and how useful have they been? What kinds of forecast information are needed? Who is likely to benefit from forecasting skill? What are the benefits of better forecasting? This book reviews what we know about these and other questions and identifies research directions toward more useful seasonal-to-interannual climate forecasts. In approaching their recommendations, the panel explores:
Keywords: Earth Sciences; Environment and Environmental Studies

Disasters by Design: A Reassessment of Natural Hazards in the United States - Mileti, Dennis (The National Academies Press, 1999)
Disasters by Design provides an alternative and sustainable way to view, study, and manage hazards in the United States that would result in disaster-resilient communities, higher environmental quality, inter- and intragenerational equity, economic sustainability, and improved quality of life. This volume provides an overview of what is known about natural hazards, disasters, recovery, and mitigation, how research findings have been translated into policies and programs; and a sustainable hazard mitigation research agenda. Also provided is an examination of past disaster losses and hazards management over the past 20 years, including factors—demographic, climate, social—that influence loss. This volume summarizes and sets the stage for the more detailed books in the series.
Keywords: Explore Science; Earth Sciences; Conflict and Security Issues

A Vision for the National Weather Service: Road Map for the Future - National Research Council (The National Academies Press, 1999)
In this study, the committee explores ways the National Weather Service (NWS) can take advantage of continuing advances in science and technology to meet the challenges of the future. The predictions are focused on the target year 2025. Because specific predictions about the state of science and technology or the NWS more than 25 years in the future will not be entirely accurate, the goal of this report is to identify and highlight trends that are most likely to influence change. The Panel on the Road Map for the Future National Weather Service developed an optimistic vision for 2025 based on advances in science and technology.
Keywords: Earth Sciences

Meeting Research and Education Needs in Coastal Engineering (The National Academies Press, 1999)
After discussions with the U.S. Army Corps of Engineers, the National Oceanic and Atmospheric Administration, the U.S. Geological Survey, and the Office of Naval Research, the National Research Council (NRC) convened a committee under the auspices of the Marine Board to examine present and anticipated national needs in coastal engineering research and education and assess the adequacy and effectiveness of existing institutions in meeting those needs.
Keywords: Earth Sciences

Strategies to Protect the Health of Deployed U.S. Forces: Medical Surveillance, Record Keeping, and Risk Reduction - Institute of Medicine (The National Academies Press, 1999)
Nine years after Operations Desert Shield and Desert Storm (the Gulf War) ended in June 1991, uncertainty and questions remain about illnesses reported in a substantial percentage of the 697,000 service members who were deployed. Even though it was a short conflict with very few battle casualties or immediately recognized disease or non-battle injuries, the events of the Gulf War and the experiences of the ensuing years have made clear many potentially instructive aspects of the deployment and its hazards. Since the Gulf War, several other large deployments have also occurred, including deployments to Haiti and Somalia. Major deployments to Bosnia, Southwest Asia, and, most recently, Kosovo are ongoing as this report is written. This report draws on lessons learned from some of these deployments to consider strategies to protect the health of troops in future deployments. In the spring of 1996, Deputy Secretary of Defense John White met with leadership of the National Research Council and the Institute of Medicine to explore the prospect of an independent, proactive effort to learn from lessons of the Gulf War and to develop a strategy to better protect the health of troops in future deployments.
Keywords: Health and Medicine

Our Common Journey: A Transition Toward Sustainability - National Research Council (The National Academies Press, 1999)
World human population is expected to reach upwards of 9 billion by 2050 and then level off over the next half-century. How can the transition to a stabilizing population also be a transition to sustainability? How can science and technology help to ensure that human needs are met while the planet's environment is nurtured and restored? Our Common Journey examines these momentous questions to draw strategic connections between scientific research, technological development, and societies' efforts to achieve environmentally sustainable improvements in human well being. The book argues that societies should approach sustainable development not as a destination but as an ongoing, adaptive learning process. Speaking to the next two generations, it proposes a strategy for using scientific and technical knowledge to better inform future action in the areas of fertility reduction, urban systems, agricultural production, energy and materials use, ecosystem restoration and biodiversity conservation, and suggests an approach for building a new research agenda for sustainability science. Our Common Journey documents large-scale historical currents of social and environmental change and reviews methods for "what if" analysis of possible future development pathways and their implications for sustainability. The book also identifies the greatest threats to sustainability—in areas such as human settlements, agriculture, industry, and energy—and explores the most promising opportunities for circumventing or mitigating these threats. It goes on to discuss what indicators of change, from children's birth-weights to atmosphere chemistry, will be most useful in monitoring a transition to sustainability.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Adequacy of Climate Observing Systems - National Research Council (The National Academies Press, 1999)
The 1997 Conference on the World Climate Research Programme to the Third Conference of the Parties of the United Nations Framework Convention on Climate Change concluded that the global capacity to observe the Earth's climate system is inadequate and is deteriorating worldwide. As a result, the chair of the subcommittee of the U.S. Global Change Research Program (USGCRP) requested a National Research Council study to assess the current status of the climate observing capabilities of the United States. This report focuses on existing observing systems for detection and attribution of climate change, with special emphasis on those systems with long time series.
Keywords: Earth Sciences; Environment and Environmental Studies

Interim Report -- Committee on Cesium Processing Alternatives for High-Level Waste at the Savannah River Site (The National Academies Press, 1999)
Keywords: Environment and Environmental Studies

Science for Decisionmaking: Coastal and Marine Geology at the U.S. Geological Survey - National Research Council (The National Academies Press, 1999)
The coastlines of the United States are beautiful places to live, work and play. But, they are also very fragile areas whose ecosystems are vulnerable to mismanagement. There are many complex issues facing the ocean science community at the federal, state and local levels—this report reflects the conclusions and recommendations of the National Academies drawing on discussions with USGS as well as input from potential users, clients and collaborators of the Coastal and Marine Geology Program.
Keywords: Earth Sciences

Funding a Revolution: Government Support for Computing Research - National Research Council (The National Academies Press, 1999)
The past 50 years have witnessed a revolution in computing and related communications technologies. The contributions of industry and university researchers to this revolution are manifest; less widely recognized is the major role the federal government played in launching the computing revolution and sustaining its momentum. Funding a Revolution examines the history of computing since World War II to elucidate the federal government's role in funding computing research, supporting the education of computer scientists and engineers, and equipping university research labs. It reviews the economic rationale for government support of research, characterizes federal support for computing research, and summarizes key historical advances in which government-sponsored research played an important role. Funding a Revolution contains a series of case studies in relational databases, the Internet, theoretical computer science, artificial intelligence, and virtual reality that demonstrate the complex interactions among government, universities, and industry that have driven the field. It offers a series of lessons that identify factors contributing to the success of the nation's computing enterprise and the government's role within it.
Keywords: Computers and Information Technology

Lighting the Way: Knowledge Assessment in Prince Edward Island - National Research Council (The National Academies Press, 1999)
Keywords: Environment and Environmental Studies

New Strategies for America's Watersheds - National Research Council (The National Academies Press, 1999)
Emergence of a toxic organism like pfisteria in tributaries of the Chesapeake Bay has focused public attention on potential hazards in our water. More importantly, it has reminded us of the importance of the entire watershed to the health of any body of water and how political boundaries complicate watershed management. New Strategies for America's Watersheds provides a timely and comprehensive look at the rise of "watershed thinking" among scientists and policymakers and recommends ways to steer the nation toward improved watershed management. The volume defines important terms, identifies fundamental issues, and explores reasons why now is the time to bring watersheds to the forefront of ecosystem management. In a discussion of scale and scope, the committee examines how to expand the watershed from a topographic unit to a framework for integrating natural, social, and economic perspectives as they share the same geographic space. The volume discusses:
Keywords: Earth Sciences; Environment and Environmental Studies

Strategies to Protect the Health of Deployed U.S. Forces: Force Protection and Decontamination - National Research Council (The National Academies Press, 1999)
Since Operation Desert Shield/Desert Storm, Gulf War veterans have expressed concerns that their postdeployment medical symptoms could have been caused by hazardous exposures or other deployment-related factors. Potential exposure to a broad range of CB and other harmful agents was not unique to Gulf operations. Hazardous exposures have been a component of all military operations in this century. Nevertheless, the Gulf War deployment focused national attention on the potential, but uncertain, relationship between the presence of CB agents in theater and symptoms reported by military personnel. Particular attention has been given to the potential long-term health effects of low-level exposures to CB agents. In the spring of 1996, Deputy Secretary of Defense John White met with the leadership of the National Academies to discuss the DoD's continuing efforts to improve protection of military personnel from adverse health effects during deployments in hostile environments. Although many lessons learned from previous assessments of Operation Desert Shield/Desert Storm have been reported, prospective analyses are still needed. Strategies to Protect the Health of Deployed U.S. Forces: Force Protection and Decontamination, which addresses the issues of physical protection and decontamination, is one of four initial reports that will be submitted in response to that request. Specifically, this report includes a review and evaluation of the following areas:
Keywords: Health and Medicine

Hydrologic Hazards Science at the U.S. Geological Survey - National Research Council (The National Academies Press, 1999)
Losses of life and property in the United States—and throughout the world—resulting from hydrologic hazards, including floods, droughts, and related phenomena, are significant and increasing. Public awareness of, and federal attention to, natural disaster reduction, with a focus on mitigation or preparedness so as to minimize the impacts of such events, have probably never been greater than at present. With over three-quarters of federal disaster declarations resulting from water-related events, national interest in having the best-possible hydrologic data, information, and knowledge as the basis for assessment and reduction of risks from hydrologic hazards is clear. The U.S. Geological Survey (USGS) plays a variety of unique and critical roles relevant to hydrologic hazard understanding, preparedness, and response. The agency's data collection, research, techniques development, and interpretive studies provide the essential bases for national, state, and local hydrologic hazard risk assessment and reduction efforts. This work includes some of the more traditional activities of the Water Resources Division (e.g., streamflow measurement) and some of the more innovative interdisciplinary activities (e.g., hydrologic research, educational outreach, real-time data transmission, and risk communication) being pursued in cooperation with other divisions of the USGS, other federal and state agencies, and other local entities. This report aims to help shape a strategy and improve the overall framework of USGS efforts in these important areas.
Keywords: Earth Sciences

Review of the Need for a Large-Scale Test Facility for Research on the Effects of Extreme Winds on Structures - National Research Council (The National Academies Press, 1999)
The Idaho National Engineering and Environmental Laboratory (INEEL), through the U.S. Department of Energy (DOE), has proposed that a large-scale wind test facility (LSWTF) be constructed to study, in full-scale, the behavior of low-rise structures under simulated extreme wind conditions. To determine the need for, and potential benefits of, such a facility, the Idaho Operations Office of the DOE requested that the National Research Council (NRC) perform an independent assessment of the role and potential value of an LSWTF in the overall context of wind engineering research. The NRC established the Committee to Review the Need for a Large-scale Test Facility for Research on the Effects of Extreme Winds on Structures, under the auspices of the Board on Infrastructure and the Constructed Environment, to perform this assessment. This report conveys the results of the committee's deliberations as well as its findings and recommendations.
Keywords: Engineering and Technology

Global Environmental Change: Research Pathways for the Next Decade - National Research Council (The National Academies Press, 1999)
How can we understand and rise to the environmental challenges of global change? One clear answer is to understand the science of global change, not solely in terms of the processes that control changes in climate and the composition of the atmosphere, but in how ecosystems and human society interact with these changes. In the last two decades of the twentieth century, a number of such research efforts—supported by computer and satellite technology—have been launched. Yet many opportunities for integration remain unexploited, and many fundamental questions remain about the earth's capacity to support a growing human population. This volume encourages a renewed commitment to understanding global change and sets a direction for research in the decade ahead. Through case studies the book explores what can be learned from the lessons of the past 20 years and what are the outstanding scientific questions. Highlights include:
Keywords: Environment and Environmental Studies; Earth Sciences

U.S. Industry in 2000: Studies in Competitive Performance - National Research Council (The National Academies Press, 1999)
U.S. industry faced a gloomy outlook in the late 1980s. Then, industrial performance improved dramatically through the 1990s and appears pervasively brighter today. A look at any group of industries, however, reveals important differences in the factors behind the resurgence—in industry structure and strategy, research performance, and location of activities—as well as similarities in the national policy environment, impact of information technology, and other factors. U.S. Industry in 2000 examines eleven key manufacturing and service industries and explores how they arrived at the present and what they face in the future. It assesses changing practices in research and innovation, technology adoption, and international operations. Industry analyses shed light on how science and technology are applied in the marketplace, how workers fare as jobs require greater knowledge, and how U.S. firms responded to their chief competitors in Europe and Asia. The book will be important to a wide range of readers with a stake in U.S. industrial performance: corporate executives, investors, labor representatives, faculty and students in business and economics, and public policymakers.
Keywords: Industry and Labor